Informal security structures and crime control and prevention in Ilorin metropolis, Nigeria - Moshood, Issah (Acta criminologica, 2017)
The formal law enforcement agencies in Nigeria continue to grapple with rising insecurity in the country albeit unsuccessfully. It is against this backdrop that this article examines the proliferation and effectiveness of informal security structures for crime control and prevention. This study draws on the Broken Windows and Defensible Space theories. Both quantitative and qualitative research methods were applied to examine the perceptions and narratives of respondents on the proliferation and effectiveness of informal security structures. A total of ten ward areas in the city of Ilorin in Nigeria were purposively selected for this study. These areas of Ilorin were: Baboko, Agbo-Oba, Surulere, Agaka, Oja-Oba, Oke-Suna, Idi-Ape, Omoda, Alfa Yahya and Oke-ebo. A total of 120 respondents were purposively selected from each of the selected areas. The total sample size was 1 200 with a questionnaire being administered to the selected respondents, supplemented by means of in-depth interviews. The quantitative data were descriptively and inferentially analysed; while the qualitative data were analysed thematically. The results indicated that the inability of the formal security structures to control and prevent the rising rates of crime and to protect life and property of Ilorin citizens has substantially contributed, in the surveyed neighbourhoods to the proliferation of informal security structures in Ilorin metropolis. Their presence has significantly reduced the rate of crime in Ilorin. Consequently, in order to make them more effective in crime control and prevention, the state government should provide the necessary support from governmental side for them in the fight against criminality in the metropolis.